2020
DOI: 10.3390/ijms21093212
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Molecular Links Between Microbiota and Gastrointestinal Cancers: A Literature Review

Abstract: Despite decades of exhaustive research on cancer, questions about cancer initiation, development, recurrence, and metastasis have still not been completely answered. One of the reasons is the plethora of factors acting simultaneously in a tumour microenvironment, of which not all have garnered attention. One such factor that has long remained understudied and has only recently received due attention is the host microbiota. Our sheer-sized microbiota exists in a state of symbiosis with the body and exerts signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 131 publications
(153 reference statements)
0
22
0
Order By: Relevance
“…One potential mechanism to explain this interaction is the joint effects of smoking and diet on the gut microbiome [ 41 ], which can in turn influence CRC risk. The main proposed mechanisms linking the microbiome with colorectal neoplasia include secretion of oncogenic microbial metabolites, such as secondary bile acids, and activation and promotion of an inflammatory response in the gut mucosa, which further promote the growth of tumor cells, and inhibit apoptosis [ 42 , 43 , 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…One potential mechanism to explain this interaction is the joint effects of smoking and diet on the gut microbiome [ 41 ], which can in turn influence CRC risk. The main proposed mechanisms linking the microbiome with colorectal neoplasia include secretion of oncogenic microbial metabolites, such as secondary bile acids, and activation and promotion of an inflammatory response in the gut mucosa, which further promote the growth of tumor cells, and inhibit apoptosis [ 42 , 43 , 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the ability of the gut microbiota to generate RNS is well discussed (for a recent review see [ 86 ]). The gut bacteria can convert nitrites into nitrosamines which have carcinogenic properties [ 87 ] and some food components present in meat and fish into trimethylamine. In the liver, trimethylamine is converted to its oxidized form (trimethylamine N -oxide) which have deleterious effects on cardiovascular and metabolic function [ 88 ].…”
Section: Response Of E Histolytica To Nitrosatmentioning
confidence: 99%
“…With the advancement of genomics and metabolomics technology, the research on the gut microbiome has gradually deepened [ 6 ]. The interaction between the intestinal microbiota and the human body was revealed, and it was also found that the intestinal microbiota is closely related to the occurrence and evolution of various diseases [ 10 12 ]. The intestinal microbiota plays an important role in the human body environment.…”
Section: Gut Microbiota and Tumor Immunitymentioning
confidence: 99%